Clinico-pathological evaluation of 37 cases of cystic fibrosis of the pancreas in infancy at necropsy - Tınaztepe, Behçet; Kural, Nurdan; Tınaztepe, Keriman; Göçmen, Ayhan (The Turkish Journal of Pediatrics, 1975)
The clinical and morphological findings of 37 cases of cystic fibrosis of the pancreas from 525 full, but non-consecutive necropsies are presented. All of these 37 cases were diagnosed at post-mortem examination. The autopsy incidence was 7 % and none of the cases was beyond two years of age. Morphological findings revealed varying severities in organ involvement in all cases, with absence of fibrosis of the pancreas in some. In only two cases histopathological changes seemed to be confined to the pancreas. This study suggests that cystic fibrosis plays a considerable role in infant deaths in our country and in most if not all cases the diagnosis must necessarily be based on postmortem studies.